Sport Specialization Characteristics Between Rural and Suburban High School Athletes - Bell, David R. (Orthop J Sports Med, 2018)
BACKGROUND: Sport specialization has been associated with overuse injuries and is more common in larger high schools, which are often located in more urban/suburban settings. However, sport participation characteristics have not been compared between suburban and rural high schools. PURPOSE/HYPOTHESIS: The purpose of this study was to examine the differences in sport participation characteristics between athletes at suburban and rural high schools. It was hypothesized that suburban high school students would be more likely to be highly specialized, participate in more athletic competitions per year, and play in a league outside of school. We also hypothesized that suburban high school students would start playing their primary sport at a younger age, would have participated in their primary sport for longer, and would play more months per year and hours per week. STUDY DESIGN: Cross-sectional study. METHODS: High school athletes from 4 high schools (2 suburban and 2 rural) participated in this study (N = 354 [222 females]; mean age, 15.7 ± 1.2 years). Athletes were on a school-sponsored athletic team in 1 of 4 sports (volleyball, tennis, basketball, soccer). The suburban schools (study enrollment, n = 226) had total school enrollments of 2271 and 622 students, while the rural schools (study enrollment, n = 128) had total school enrollments of 443 and 297. Participants completed a questionnaire prior to the start of their high school sport season. The questionnaire consisted of demographic information, a sport specialization scale, and sport participation information. Primary sport competition volume in the previous 12 months was classified as high (>60 primary sport competitions), moderate (30-60), or low (<30). Sport specialization status was classified via a 3-point scale as low, moderate, or high. RESULTS: As compared with athletes at rural schools, athletes at suburban schools started playing their primary sport at a younger age (suburban, 7.8 ± 2.9 years; rural, 9.7 ± 3.2 years; P < .001) and participated for more years (suburban, 7.9 ± 3.1 years; rural, 6.1 ± 3.3 years; P < .001), more months per year (suburban, 7.6 ± 3.6 months; rural, 5.6 ± 2.8 months; P < .001), and more hours per week (suburban, 15.2 ± 5.1 hours; rural, 12.9 ± 3.3 hours; P < .001). Athletes at suburban schools were more likely than rural athletes to be classified as highly specialized (χ(2) = 52.5, P < .001), participate in more competitions (χ(2) = 16.5, P < .001), play in a league outside of school (χ(2) = 18.4, P < .001), and train in their primary sport for >8 months per year (χ(2) = 27.8, P < .001) and >16 hours per week (χ(2) = 15.0, P < .001). CONCLUSION: High school athletes at suburban schools are more likely to exhibit sport participation patterns that are associated with increased risk of overuse injury. These include being classified as highly specialized, playing their primary sport >8 months per year and >16 hours per week, engaging in a high competition volume, and participating in a sport league (eg, club) outside of school. Efforts aimed at safe sport participation should target these groups, as they seem more likely to violate safe sport recommendations.